In praise of God: sport as worship in the practice and self-understanding of elite athletes - Ellis, R; Weir, JS (MDPI, 2020)
The relationships between sport and religion have been examined from a number of perspectives, and parallels between sporting activity and worship are often observed, positively or negatively. Elite sports participants often perform religious gestures and many speak of their sporting performance in terms of their religious faith, including the assertion that it constitutes an act of worship. The authors begin by considering the nature of Christian worship, examining worship as a phenomenon, key biblical and theological ideas, the relationship of worship to sacred places and times, and the relation of worship to everyday life. The self-understanding of elite athletes of faith is then considered, as articulated in interviews collected over several years with one of the authors and in other published statements. This data is then mapped back on to the previously considered ideas of worship. The article suggests that, while the correspondence may not be complete or exact, there is good reason to take seriously the claims of elite athletes of faith that their sporting performance should be regarded as an act of worship.